Combining SRQ20 and PHQ9 for tackling mental problem in community - Hikmawati Nurokhmanti; Fitriana Fitriana; Irwan Supriyanto (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Mental health influences people’s productivity from individual-level to enterprise level. This important factor should be assessed and tackled by the primary care unit since healthy community is their ultimate goal. Sixty of two screening tools (self-rating questionnaire [SRQ20] and patient health questionnaire [PHQ9]) were randomly distributed by primary care unit through cadres at Kricak, Tegalrejo District to community which is attending the cadre launching. SRQ had an 83,33% response rate, whereas PHQ9 has only 41,7% response rate. By comparative distributive analysis, it was found that one person who fallen into moderately severe symptoms of depression in PHQ9 was had not fallen into the person who has mental problem based on SRQ20, and two persons who fall into the moderate symptom of depression in PHQ9 were had not fallen into person who has mental problem based on SRQ20. There was 20% inconsistency between the two tools of mental health assessment. Using two tools assessing mental health problem is fruitful since it will cover each other. This study proved that there could be divergent result from both questionnaires. A decision before continuity management care of depression should be taken carefully. There should be another step taken by primary care unit before they undergo management care for depression.